Associations between oral sex practices and frequent mouthwash use in heterosexuals: a cross-sectional survey in Melbourne, Australia - Phillips, Tiffany R (BMJ Open, 2021)
OBJECTIVE: This study aimed to determine the frequency of mouthwash use and its association to oral sex practice in heterosexuals. DESIGN: A cross-sectional study. SETTING: Data obtained from a sexual health clinic in Victoria, Australia, between March 2019 and April 2019. PARTICIPANTS: Heterosexual men and women attending the sexual health clinic answered a survey using computer-assisted self-interview. PRIMARY AND SECONDARY OUTCOME MEASURES: Univariable and multivariable logistic regression were performed to examine the association between frequent mouthwash use (ie, daily or weekly mouthwash use) and oral sex practices (including tongue kissing, fellatio, cunnilingus and insertive rimming). RESULTS: There were 681 heterosexuals included in the analysis: 315 (46.3%) men and 366 (53.7%) women. Of participants, 302 (44.3%) used mouthwash frequently, 173 (25.4%) used mouthwash infrequently and 206 (30.2%) never used mouthwash. There was no significant difference in the proportion of frequent mouthwash users between men and women (46.4% of men vs 42.6% of women; p=0.329). The proportion of frequent mouthwash users increased with increasing age groups (39.3% in [Formula: see text] 24 years, 45.2% in 25–34 years and 52.8% in [Formula: see text] 35 years or older; p(trend)=0.039) with those aged [Formula: see text] 35 years having a 1.80 times (95% CI: 1.12 to 2.89) higher odds of being a frequent mouthwash user than those aged ≤24 years. There were no significant associations between frequent mouthwash users had sexually transmitted infection (STI) risk after adjusting for age and country of birth. CONCLUSION: Older heterosexuals are more likely to use mouthwash. Given the high proportion and associations of mouthwash use in heterosexuals, future investigations related to oral STIs in this group should include mouthwash use.